Teclistamab versus real-world physician's choice of therapy in triple-class exposed relapsed/refractory multiple myeloma - Amrita Krishnan; Ajay K Nooka; Ajai Chari; Alfred L Garfall; Thomas G Martin; Sandhya Nair; Xiwu Lin; Keqin Qi; Anil Londhe; Lixia Pei; Eric Ammann; Rachel Kobos; et al. (Becaris Publishing Limited, 2023)
Aim: We compared the effectiveness of teclistamab versus real-world physician's choice of therapy (RWPC) in triple-class exposed relapsed/refractory multiple myeloma. Materials & methods: MajesTEC- 1 eligibility criteria were applied to the RWPC cohort. Baseline covariate imbalances were adjusted using inverse probability of treatment weighting. Overall survival, progression-free survival and time to next treatment were compared. Results: After inverse probability of treatment weighting, baseline characteristics were similar between cohorts (teclistamab, n = 165; RWPC, n = 364 [766 observations]). Teclistamab treated patients had numerically better overall survival (hazard ratio [HR]: 0.82 [95% CI: 0.59- 1.14]; p = 0.233) and significantly greater progression-free survival (HR: 0.43 [0.33-0.56]; p < 0.0001) and time to next treatment (HR: 0.36 [0.27-0.49]; p < 0.0001) versus the RWPC cohort. Conclusion: Teclistamab offered clinical benefit over RWPC in triple-class exposed relapsed/refractory multiple myeloma.